A New Method to Purify Hydroxyl Monascus Red Pigment by Retrogradation of Both Pigments and Maize Amylopectin. (27th February 2019) - Lian, Xijun; Li, Min; Jiang, Rongxia; Guo, Junjie; Feng, Zhao
Abstract : In monascus red pigment (MRP) products, there exist many components such as polypeptides, amino acids, polysaccharide, and citrinin (toxin). The existence of those components lowers the purity of pigments and brings a great security problem. Hydroxyl MRP has been found in products of China and other countries. This paper presents a new method to isolate hydroxyl MRP by retrograded maize amylopectin (MA) and proposes the mechanism involved based on investigation of Xray‐diffraction, IR and 13 C solid NMR spectra. The research results have shown that the optimum retrogradation parameters for purification of hydroxyl MRP are as follows: the ratio of pigments and MA is 1:1, autoclaving temperature 120 °C and time, 20 min, aging temperature 4 °C and time needed, 48 h. Most non‐pigment components without hydroxyls in the samples are dissolved in solution when retrograded MA containing MRP has been hydrolyzed by amylase with only MA and MRP left in the precipitatate. Such precipitation can redissolve in aqueous KOH to open hydrogen bond and the MA in solution can be distilled by ethanol in neutral pH, and then the purified pigments in solution can be concentrated and dried. Every 100 g MA can isolate 68.0 g MRP. The results of IR and 13 C solid NMR have indicated that hydrogen bonds might form between C7 of pigment and C1 of MA, also, C10 of pigment and C3 or C2 of MA. Retrogradation is surely a simple, inexpensive, and valid method to isolate pigments with hydroxyl groups and citrinin. Abstract : The authors mix maize amylopectin with hydroxyl MRP and the obtained retrograded amylopectin belonging to pigments is insoluble in water, pigments are separated from those water soluble impurities. And then the retrograded amylopectin can re‐dissolve in 4 M KOH, after that amylopectin is precipitated by addition of ethanol, thus the hydroxyl pigments are purified.